2023
DOI: 10.3390/audiolres13040047
|View full text |Cite
|
Sign up to set email alerts
|

Management of Migraine-Associated Vestibulocochlear Disorders

Abstract: Migraine is a chronic neurological disorder that frequently coexists with different vestibular and cochlear symptoms (sudden hearing loss, tinnitus, otalgia, aural fullness, hyperacusis, dizziness, imbalance, and vertigo) and disorders (recurrent benign positional vertigo, persistent postural perceptual dizziness, mal de debarquement, and Menière’s disease). Despite evidence of an epidemiological association and similar pathophysiology between migraine and these vestibulocochlear disorders, patients suffering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 123 publications
0
1
0
Order By: Relevance
“…Additionally, research has demonstrated that a higher prevalence of sleep disorders in individuals with fibromyalgia or migraine (45). Furthermore, hyperstimulation of dorsal horns of the cervical spine and trigeminal nucleus has been linked to the development of chronic fibromyalgia (46,47). Symptoms such as aural fullness and otalgia may be related to trigeminal nerve activation and cortical oversensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research has demonstrated that a higher prevalence of sleep disorders in individuals with fibromyalgia or migraine (45). Furthermore, hyperstimulation of dorsal horns of the cervical spine and trigeminal nucleus has been linked to the development of chronic fibromyalgia (46,47). Symptoms such as aural fullness and otalgia may be related to trigeminal nerve activation and cortical oversensitivity.…”
Section: Discussionmentioning
confidence: 99%